Impact of pulmonary hypertension on mortality in progressive massive fibrosis - Özgün, Serhat; Sarı, Gülden; Koyuncu, Adem; Ezber, Rabia; Arslan, Mücahid Alp; Doğan, Fatih Mehmet; Koç, Şahbender; Şimşek, Ceprail (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background and aim: The aim of this study was to investigate the factors affecting the development of pulmonary hypertension (PH) in patients with progressive massive fibrosis (PMF) and to determine the relationship between PH development and life expectancy. Methods: In this retrospective study, 181 patients with PMF were recruited over a 9-year period and 96 were eligible for analysis. We used echocardiography (ECHO) findings to estimate the likelihood of developing PH. We used Bernoulli’s equation with tricuspid regurgitation velocity measurement and calculated systolic pulmonary artery pressure (sPAP) by adding the estimated right atrial pressure. We accepted sPAP values of 37 and 50 mm Hg as criteria for moderate and high probability PH. Results: The prevalence of moderate or high probability PH (PH group) was 29.1% in patients with PMF. Older age (OR:1.059, p=0.036) and presence of C opacity (OR:4.607, p=0.024) were found to be risk factors for PH in patients with PMF. The survival rate (39.2%) and mean survival time (65.20±9.94 months) were significantly lower in the PH group compared to the non-PH group (p=0.002). PH development was primarily associated with fibrotic disease burden rather than coexisting airflow obstruction. Conclusions: The development of PH and the increase in the degree of PH have a negative effect on the mean survival time. Preventing the development of PMF, which has a poor prognosis, by taking necessary precautions is the most effective option in treatment.